2022
DOI: 10.3390/antiox11050908
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin-Induced Apoptotic Cell Death in Human SH-SY5Y Cells Involves the Activation of Oxidative Stress and Mitochondrial Pathway and Akt/mTOR-Pathway-Mediated Autophagy

Abstract: Ivermectin (IVM) could cause potential neurotoxicity; however, the precise molecular mechanisms remain unclear. This study explores the cytotoxicity of IVM in human neuroblastoma (SH-SY5Y) cells and the underlying molecular mechanisms. The results show that IVM treatment (2.5–15 μM) for 24 h could induce dose-dependent cell death in SH-SY5Y cells. Compared to the control, IVM treatment significantly promoted the production of ROS, mitochondrial dysfunction, and cell apoptosis. IVM treatment also promoted mitop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…To observe the nuclear morphological change, HepG2 cells were also stained with Hoechst 33342, according to our previous study [ 26 ]. In brief, HepG2 cells were treated with CHE at the various concentrations of 2.5, 5, and 10 μM for 24 h and were stained with Hoechst 33342 dye (at the final concentration of 10 μg/mL) for 30 min in the dark at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To observe the nuclear morphological change, HepG2 cells were also stained with Hoechst 33342, according to our previous study [ 26 ]. In brief, HepG2 cells were treated with CHE at the various concentrations of 2.5, 5, and 10 μM for 24 h and were stained with Hoechst 33342 dye (at the final concentration of 10 μg/mL) for 30 min in the dark at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The levels of caspase-9 and caspase-3 activities in HepG2 cells were examined using commercial caspase-9 and caspase-3 kits (Beyotime, Haimen, China), respectively. The detailed protocols were in line with our previous study [ 26 ]. In brief, HepG2 cells were treated with different doses of CHE (i.e., at 1.25, 2.5, 5, and 10 μM, respectively).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ivermectin, a drug used in parasitic infections, has recently been linked to disinformation related to its efficacy against SARS-CoV-2. Zhang et al raised further awareness against self-medication and unsupervised use of ivermectin beyond the scope of its primary application, with an in vitro study linking this drug to neurotoxicity [ 12 ]. In this toxicological study, human neuroblastoma-derived SH-SY5Y cells were treated with increased doses of ivermectin, resulting in increased production of reactive oxygen species, mitochondrial dysfunction, and autophagy.…”
mentioning
confidence: 99%
“…In this toxicological study, human neuroblastoma-derived SH-SY5Y cells were treated with increased doses of ivermectin, resulting in increased production of reactive oxygen species, mitochondrial dysfunction, and autophagy. The authors further identified the inhibition of the Akt–mTOR pathway as the cause of the apoptotic and autophagic events in this cell line [ 12 ].…”
mentioning
confidence: 99%